An inflammatory-CCRK circuitry drives mTORC1-dependent metabolic and immunosuppressive reprogramming in obesity-associated hepatocellular carcinoma. Issue 1 (December 2018) - Sun, Hanyong; Yang, Weiqin; Tian, Yuan; Zeng, Xuezhen; Zhou, Jingying; Mok, Myth; Tang, Wenshu; Feng, Yu; Xu, Liangliang; Chan, Anthony; Tong, Joanna; Cheung, Yue-Sun; et al.
Abstract Obesity increases the risk of hepatocellular carcinoma (HCC) especially in men, but the molecular mechanism remains obscure. Here, we show that an androgen receptor (AR)-driven oncogene, cell cycle-related kinase (CCRK), collaborates with obesity-induced pro-inflammatory signaling to promote non-alcoholic steatohepatitis (NASH)-related hepatocarcinogenesis. Lentivirus-mediatedCcrk ablation in liver of male mice fed with high-fat high-carbohydrate diet abrogates not only obesity-associated lipid accumulation, glucose intolerance and insulin resistance, but also HCC development. Mechanistically, CCRK fuels a feedforward loop by inducing STAT3-AR promoter co-occupancy and transcriptional up-regulation, which in turn activates mTORC1/4E-BP1/S6K/SREBP1 cascades via GSK3β phosphorylation. Moreover, hepaticCCRK induction in transgenic mice stimulates mTORC1-dependentG − csf expression to enhance polymorphonuclear myeloid-derived suppressor cell recruitment and tumorigenicity. Finally, the STAT3-AR-CCRK-mTORC1 pathway components are concordantly over-expressed in human NASH-associated HCCs. These findings unveil the dual roles of an inflammatory-CCRK circuitry in driving metabolic and immunosuppressive reprogramming through mTORC1 activation, thereby establishing a pro-tumorigenic microenvironment for HCC development. Obesity increases the risk of hepatocellular carcinoma (HCC) especially in men. Here the authors find a potential mechanistic explanation by showing that, in mice, obesity-induced STAT3 cooperates with the androgen receptor to activate the mTORC pathway through up regulation of CCRK, resulting in hepatic steatosis worsening and HCC development via metabolic and immune reprogramming.